A Dr Johnson Chronology - Page, Norman. author. aut Link
XV, 136 p.
Keywords: This chronology, like others in the series, presents the story of Dr Johnson's life in a readily accessible format to provide scholar and general reader alike with a quick guide to dates, people and places together with supplementary indexes.